Application of principal component and hierarchical cluster analysis to classify different edible Cucurbita based on in vitro antioxidant activity - Mitić Violeta; Nikolić Jelena; Dimitrijević Marija; Stankov-Jovanović Vesna; Stojanović Gordana (Journal of the Serbian Chemical Society)
This study investigated the variations in antioxidant profiles between nine edible Cucurbita species (pericarp and seed), using pattern recognition tools; classification was achieved based on the results of global antioxidant activity assays (DPPH, ABTS, FRAP, CUPRAC, total reducing of power, levels of total phenolics and flavonoids compounds). The pericarp samples showed significantly lower total phenol values than the seed samples. The spaghetti squash shows the highest ability to neutralize DPPH radicals among seed and pericarp extracts. This extract also shows the highest FRAP and CUPRAC values. The tested samples were grouped into pericarp extract groups and seed extract groups based on the principal component analysis of antioxidative profiles. Hierarchical cluster analysis confirmed the PCA analysis. Тhe presented results can guide breeders in selecting Cucurbita varieties with enhanced antioxidant traits, contributing to the development of nutritionally superior crops.